1993
DOI: 10.1093/nar/21.9.2165
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for efficient translational frameshifting in the synthesis of the putative viral RNA-dependent RNA polymerase of potato leafroll virus

Abstract: The putative RNA-dependent RNA polymerase of potato leafroll luteovirus (PLRV) is expressed by -1 ribosomal frameshifting in the region where the open reading frames (ORF) of proteins 2a and 2b overlap. The signal responsible for efficient frameshift is composed of the slippery site UUUAAAU followed by a sequence that has the potential to adopt two alternative folding patterns, either a structure involving a pseudoknot, or a simple stem-loop structure. To investigate the structure requirements for efficient fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…The 255 nt of the PVY-derived RNA probe (Fig. I b) used for electrophoretic mobility-shift, UV crosslinking and competition assays were prepared by in vitro transcription (Kujawa et al, 1993) of BstEII-digested pT7:HCA699 with T7 RNA polymerase (Gibco BRL) in the presence of 50 gCi of [c~-3aP]CTP. For Northwestern blot assays, in addition to the above mentioned probe, a 32P-labelled non-specific RNA probe corresponding to the first 200 nt of the 5' region of TYMV was obtained by in vitro transcription with T7 RNA polymerase of SnaBI-digested pTA216 as described above (generating probe A'200).…”
Section: Methodsmentioning
confidence: 99%
“…The 255 nt of the PVY-derived RNA probe (Fig. I b) used for electrophoretic mobility-shift, UV crosslinking and competition assays were prepared by in vitro transcription (Kujawa et al, 1993) of BstEII-digested pT7:HCA699 with T7 RNA polymerase (Gibco BRL) in the presence of 50 gCi of [c~-3aP]CTP. For Northwestern blot assays, in addition to the above mentioned probe, a 32P-labelled non-specific RNA probe corresponding to the first 200 nt of the 5' region of TYMV was obtained by in vitro transcription with T7 RNA polymerase of SnaBI-digested pTA216 as described above (generating probe A'200).…”
Section: Methodsmentioning
confidence: 99%
“…For proper estimates of the parameters in the formulas, we used some sequences of known pseudoknots that are evidenced by experiments and/or phylogenetic comparisons, assuming that the free energies of these pseudoknots are lower than those of corresponding hairpins formed by the pseudoknot stems+ As seen in Table 1, these H-pseudoknots cover rather broad ranges of loop and stem sizes+ The majority of pseudoknots, available for analysis, are found in viral RNAs (ten Dam et al+, 1990;Deiman & Pleij, 1997) and representative structures are shown in Figure 2+ The large group of well-documented H-pseudoknots are found at the very 39 ends of plant viral RNAs (tymoviruses and tobamoviruses) as parts of tRNA-like structures (for review, see, e+g+, Mans et al+, 1991)+ These pseudoknots seem to have minimal loop sizes and show little variation in stem lengths, with a stem S1 of 3 bp and S2 of 4 bp in tobamoviruses and 5-6 bp in tymoviruses (Fig+ 2A)+ Upstream of the tRNA-like structure in tobamoviruses, a conserved structure of three consecutive pseudoknots is located (Fig+ 2B), which seems to be very important in regulation of viral multiplication and mRNA translation (van Belkum et al+, 1985;Leathers et al+, 1993)+ Those three pseudoknots or only two are duplicated in some tobamoviruses and satellite tobacco mosaic virus, sometimes with a considerable sequence variation (Gultyaev et al+, 1994)+ Similar pseudoknot stalks are conserved in some hordei-, furoand tobraviruses and satellite tobacco necrosis viruses STNV-1 and STNV-2 (Pleij et al+, 1986;Danthinne et al+, 1991;Solovyev et al+, 1996;Koenig et al+, 1998), with different numbers of pseudoknots (Table 1)+ The biggest variation in the sizes of pseudoknot loops and stems is observed in the sites of pseudoknot-dependent ribosomal frameshift and readthrough (ten Dam et al+, 1990;Brierley et al+, 1991;Chamorro et al+, 1992;Garcia et al+, 1993;Kujawa et al+, 1993;Wills et al+, 1994)+ Although large pseudoknot loops, like those found in frameshift sites of coronaviruses (Fig+ 2E), may have an interior structure, we included them in our analysis to test the performance of logarithmic extrapolation+ For each analyzed pseudoknot, the condition of lower free energy than that of either of two hairpins formed separately by stems S1 or S2 (Fig+ 1) leads to the requirement that the sum of loop energies be less than some computable value+ In these calculations, possible coaxial stacking on stems adjacent to the pseudoknots, as in 39-terminal tRNA-like structures or pseudoknot stalks (Fig+ 2A,B), was also taken into account+ Possible extensions of stems, when they are formed separately, were also considered+ Also, in case of...…”
Section: Estimates Of Loop Energies Using Proven Pseudoknotsmentioning
confidence: 96%
“…The suggested set of parameters predicts that all considered 39-terminal pseudoknots in the plant viral tRNA-like structures (e+g+, Fig+ 2A) are more stable than alternative hairpins, with differences in the range of 2-5 kcal/mol+ The individual stabilities of consecutive pseudoknots in the stalks (Fig+ 2B) are more difficult to determine, because of coaxial stacking contributions between them+ Nevertheless, the values given in Table 2 clearly define the pseudoknot stalks as the most stable structures in these regions+ The more conserved pseudoknots PK2 and PK3, which are probably more important (Leathers et al+, 1993), are mostly more stable as well+ However, the 59-proximal pseudoknots are also predicted to be energetically more favorable than the hairpins formed by S2 stems, although the S1 stems in these pseudoknots are not stabilized by coaxial stacking on the 59-side+ Ribosomal frameshift sites in the polymerase genes from luteoviruses (Fig+ 3) provide an interesting test case for energy parameters+ The presence of homologous pseudoknots in the analyzed sequences is supported by nucleotide base-base covariations in both pseudoknot stems+ There is also experimental evidence of pseudoknot involvement in the frameshifting signals of beet western yellows virus (BWYV) and potato leafroll virus (PLRV) genes (Garcia et al+, 1993;Kujawa et al+, 1993)+ However, in one of the PLRV strains and in cucurbit aphid-borne yellows virus (CABYV), the pseudoknot seems to be destabilized by a mismatch at the junction (Fig+ 3C,D)+ Also, in a German isolate of PLRV (PLRV-G) an alternative stemloop structure (Fig+ 3E) was suggested (Prüfer et al+, 1992)+ Our set of free energy values (Table 2) predicts that in all sequences, the pseudoknots are more stable than the alternate S1 or S2 hairpins, even in the two cases with mismatches+ The alternative structure in the German strain is predicted to be only 3+7 kcal/mol more stable at 25 8C than the pseudoknot+ However, its existence may be doubted, because it comprises an additional 24 nt downstream of the pseudoknot and could be disrupted because of competition with other downstream foldings+ It is interesting that particularly in this PLRV variant (Prüfer et al+, 1992) the pseudoknot is also stabilized by an additional G-C pair in the S2 stem (Fig+ 3E)+ Pseudoknots at the sites of ribosomal frameshifting and readthrough in animal viruses contain stems with many G-C pairs (Fig+ 2D-F) and seem to be very stable+ All analyzed pseudoknots are estimated to have considerably lower free energies than the alternate hairpins+ In case of readthrough sites from type C retroviruses and frameshifting sites from coronaviruses, both the loops and the stems of pseudoknots are relatively big ( Table 1), so that the pseudoknots comprise rather extended RNA regions that provide opportunities for other alternative foldings+ We compared the estimated pseudoknot free energies with the predicted stabilities of such structures+ It turned out, however, that only one (MoMuLV) of the five different readthrough sequences was folded into a structure with free energy equal to …”
Section: Predicted Stability Of Natural Pseudoknotsmentioning
confidence: 99%
“…Such expression strategies (for a review see ref. 27) have been studied in detail with luteoviruses and include Ϫ1 ribosomal frameshifting (28)(29)(30)(31), amber stop-codon suppression (32)(33)(34), and cap-independent translation initiation (35, 36).…”
mentioning
confidence: 99%